The Interaction in the Learning of the Mathematics: Teachers’ Stories - Carneiro-Abrahão, Ana Maria; Universidad del Estado de Rio de Janeiro (Pontificia Universidad Javeriana, 2007)
This work is product of the analysis of stories presented by twenty-two teachers who decided to share their classroom experiences of mathematics education considered by them like successful. One looks for analyzing the forms of teachers understanding what it is “to be successful” during the process of “mathematizing”, seen like a reflective activity of education that looks for to understand and to modify the reality. The study reveals that the pedagogical practice that considers problems rooted in the concrete experiences of the daily life, besides to reveal the reality of the school, it takes to the teacher to reflect on its practice and on the accomplishment of “didactic mediation” that promotes more pleasant teaching-learning situations that can elevate the student self-esteem.